Clinical pregnancy derived of blastocyst culture and transfer at Permata Hati Infertility Clinic Dr Sardjito Hospital/Faculty of Medicine Gadjah Mada University Yogyakarta. A case report - Ita Haryadi Ita Haryadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
In the natural environment, human embryos will be only in the uterine cavity at the morula or blastocyst stage. However, in vitro culture of embryos in assisted reproductive technologies remain replacing back embryos at or before four cell stage due to some problems involved. In this case report we aimed to culture and transfer embryos at blastocyst stage. A sub-fertility couple, wife at 33 years old, with bilateral fallopian tube damage. Husband has normal semen analysis. Of 9 oocytes retrieved from ovum pick up (OPU), seven were fertilized. On day 3 observation, five embryos showing considerably good in grade to allow further development. On day 5, four out of 5 embryos were formed blastocysts of which 2 were transferred, and the other two blastocysts were cryopreserved. Blastocysts of this reported patient were formed at the rate of 57.1% (4/7). Pregnancy was confirmed by positive urine semi-quantitative test, two intrauterine gestational sacs with 3 heart pulsations detected by ultrasonography. We reported a pregnancy obtained from our first human blastocyst culture and transfer to the couple undergoing in vitro fertilization (IVF) program at Permata Hati Infertility Clinic, DR Sardjito Hospital/Faculty of Medicine Gadjah Mada University, Yogyakarta.Key words : blastocyst culture - assisted reproductive technologies - in vitro fertilization